Intramolecular thiol-yne cyclisation as a novel strategy for thioglycal synthesis - SCANLAN, EOIN (My University, 2015)
A novel intramolecular thiol–yne cyclisation strategy has been developed for the synthesis of thioglycals. Both ionic and radical mediated cyclisation pathways have been investigated for D- and L-sugars. The ionic cyclisation provides exclusive access to 5-exo products directly from the thioesters whereas the radical cyclisation provides access to both 5-exo and 6-endo products upon photochemical irradiation of the free thiols. These are the first examples of intramolecular thiol–yne cyclisation reactions applied to thiosugar synthesis.
Keywords: intramolecular thiol–yne cyclisation; intramolecular thiol–yne cyclisation